2019
DOI: 10.1016/s0140-6736(19)32596-6
|View full text |Cite
|
Sign up to set email alerts
|

The 2019 report of The Lancet Countdown on health and climate change: ensuring that the health of a child born today is not defined by a changing climate

Abstract: The next decade is likely to produce any number of global challenges that will affect health and health care, including pan-national infections such as the new coronavirus COVID-19 and others that will be related to global warming. Nurses will be required to react to these events, even though they will also be affected as ordinary citizens. The future resilience of healthcare services will depend on having sufficient numbers of nurses who are adequately resourced to face the coming challenges.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

10
774
0
39

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 1,109 publications
(900 citation statements)
references
References 104 publications
10
774
0
39
Order By: Relevance
“…Compounding its exposure to climate change, Jakarta is also one of the fastest sinking cities in the world, with parts of the city having sunk by up to 4 m since leveling surveys began in 1978 (Abidin et al, 2001(Abidin et al, , 2011. This sinking makes Jakarta vulnerable to flooding, tsunamis, and intense coastal storms expected to increase in frequency in this area due to climate change (Knutson et al, 2012;Siagian et al, 2014;Thiede and Gray, 2017;Watts et al, 2019). Furthermore, Jakarta is located on the island of Java where there is overall limited sustainability.…”
Section: Abstract: Anthropocene Biodiversity Flooding Impacts Indmentioning
confidence: 99%
“…Compounding its exposure to climate change, Jakarta is also one of the fastest sinking cities in the world, with parts of the city having sunk by up to 4 m since leveling surveys began in 1978 (Abidin et al, 2001(Abidin et al, , 2011. This sinking makes Jakarta vulnerable to flooding, tsunamis, and intense coastal storms expected to increase in frequency in this area due to climate change (Knutson et al, 2012;Siagian et al, 2014;Thiede and Gray, 2017;Watts et al, 2019). Furthermore, Jakarta is located on the island of Java where there is overall limited sustainability.…”
Section: Abstract: Anthropocene Biodiversity Flooding Impacts Indmentioning
confidence: 99%
“…We must live in this planet, there is no other Earth or planet/plan B. And we have observed that air pollution and Planetary Health can be improved within weeks, with concerted individual and societal efforts [6]. Children confined at home for 3 weeks already, have appreciated playing with their brothers and sisters, or talking with neighbors across the balconies; even remotely with their school friends and teachers.…”
mentioning
confidence: 99%
“…Sustained warmer temperatures at higher latitudes affect the geographic ranges of infectious microorganisms and their vectors, resulting in greater numbers of people at risk for infectious diseases, including many with dermatologic manifestations. 2 Mass human migration from newly inhospitable areas decreases healthcare access, lowers vaccination rates, limits access to clean water, impairs hygiene, and leads to overcrowding and disease transmission. 2 By 2100, if emission trends continue, climate change is expected to cause an additional 1.5 million deaths annually, worldwide.…”
mentioning
confidence: 99%
“…2 Mass human migration from newly inhospitable areas decreases healthcare access, lowers vaccination rates, limits access to clean water, impairs hygiene, and leads to overcrowding and disease transmission. 2 By 2100, if emission trends continue, climate change is expected to cause an additional 1.5 million deaths annually, worldwide. 3 As of late April 2020, approximately 200,000 people have died from COVID-19.…”
mentioning
confidence: 99%
See 1 more Smart Citation